Pretrial Risk Assessment, Release Recommendations, and Racial Bias - Zottola, Samantha A. (Criminal justice and behavior, 2023)
We examined how the presentation of risk assessment results and the race of the person charged affected pretrial court actors’ recommendations to release a person with or without conditions. A sample of 246 pretrial court actors read vignettes that varied risk framing (success, failure), risk format (probability, frequency), risk level (low, high), and race of the person charged (Black, White). Pretrial release recommendations did not differ as a function of framing or format overall or by race. Pretrial court actors were more likely to recommend release with conditions compared with release without conditions in the high- versus low-risk groups when the person was White but not when the person was Black. Findings fail to support changes to the presentation of pretrial risk assessment results as strategies to enhance their impact on release recommendations and underscore the need for efforts to ensure equitable application of risk assessment results for people of color.